An Ultrafast, High‐Loading, and Durable Poly(p‐aminoazobenzene)/Reduced Graphene Oxide Composite Electrode for Supercapacitors. (26th January 2023) - Ai, Zhiting; Li, Lu; Huang, Muyun; Su, Xiaofang; Gao, Yanan; Wu, Jifeng
Abstract: Although challenging, the fabricated supercapacitor electrodes with excellent rate capability, long cycling stability, and high mass‐loading are crucial for practical applications. Herein, a novel 3D porous poly(p‐aminoazobenzene)/reduced graphene oxide hydrogel is designed and prepared as an ultrafast, high‐loading, and durable pseudocapacitive electrode through a facile two‐step self‐assembly approach. Owing to abundant stable redox‐active sites, fast electrolyte diffusion, and efficient charge conduction, the PRH electrode (5 mg cm −2 ) shows a high specific capacitance (701 F g −1 at 2 A g −1 ) and ultrafast rate (97% capacitance retention at 100 A g −1 ). Furthermore, even with a mass‐loading of 10 mg cm −2, the electrode still exhibits comparable high performance and excellent long‐term cycling life (only 6.7% capacitance loss after 10 000 cycles). This work demonstrates novel polyaniline analog composites for constructing novel electrodes, promising to open an avenue toward practical applications. Abstract : Polyaniline‐based supercapacitors are limited by poor rate capability, undesirable cycling stability, and low mass‐loading. Hence, a novel 3D polyaniline analog‐based composite is proposed as a pseudocapacitive electrode. The prepared high‐loading electrodes possess abundant stable redox‐active sites and porous conductive nanostructure, solving the problem of sluggish charge conduction, slow electrolyte diffusion, and inferior cycling stability.